Future spatial modeling of vegetation in the Central Atlantic Forest Corridor, Brazil - de Santana, Romário Oliveira; Delgado, Rafael Coll; Schiavetti, Alexandre (Frontiers in Conservation Science, 2022)
Tropical forests stand out among forest domains, due to their wide diversity of flora and fauna. However, these areas concentrate a large number of the forest fires that occur annually on the planet. In this context, the present study performs spatial modeling of the normalized multi-band drought index (NMDI) in the Central Atlantic Forest Corridor during past (2001-2020) and future (2021-2040) periods to identify the relationship between drought and forest fires. Fire foci data, soil moisture, and data from the MOD09A1 product were used to obtain the NMDI. Rainfall and mean air temperature data from the past and for different future scenarios (SSP126 and SSP585) were also used. The autoregressive integrated moving average model (ARIMA) was used for modeling the NMDI. The results found indicate a recurrence of fire in the CAFC during the period of 2001–2020. Future data indicate reductions in rainfall and an increase in temperature in the CAFC area. The NMDI data indicate that the central region of the corridor is the driest and, among the priority areas for conservation, the Ilha do Lameirão Municipal ecological station has the lowest index values. Future modeling indicates the drought intensifying in the coming years in the corridor area. The CAFC is an extremely important area for the maintenance of Atlantic Forest remnants; however, this area continues to suffer disturbances and without the adoption of public policies, these disturbances could compromise the conservation of natural resources.